Design of Binary Cu–Fe Sites Coordinated with Nitrogen Dispersed in the Porous Carbon for Synergistic CO2 Electroreduction. Issue 4 (29th December 2020) - Yun, Ruirui; Zhan, Feiyang; Wang, Xinjian; Zhang, Beibei; Sheng, Tian; Xin, Zhifeng; Mao, Junjie; Liu, Shoujie; Zheng, Baishu
Abstract: To relieve the green gas emission and involve the carbon neutral cycle, electrochemical reduction of CO2 attracts more and more attention. Herein, a biatomic site catalyst of Cu–Fe coordinated with the nitrogen, which is doped in the carbon matrix (denoted as Cu–Fe–N6 –C), is designed. The as‐obtained Cu–Fe–N6 –C exhibits higher performance than that of Cu–N–C and Fe–N–C, owing to bimetallic sites, proving synergistic functions based on different molecules and their interfaces. Cu–Fe–N6 –C shows high selectivity toward CO, with high Faradaic efficiency (98% at −0.7 V), and maintaining 98% of its initial selectivity after 10 h electrolysis. The experimental results and theoretical calculations reveal that the synergistic catalysis of different metallic sites enlarges the adsorption enthalpy of CO2, reducing the activation energy result in generating high selectivity, activity, stability, and low impedance. Abstract : A binary Cu–Fe site catalyst of Cu–Fe–N6 –C is synthesized and used in the reduction of CO2 with high selectivity toward CO and high Faradaic efficiency. The theoretical calculations unveil that the synergistic catalysis of different metallic sites can facilitate the CO2 adsorption and reduce the CO bond breaking barrier result in generating high selectivity and activity.